Seasonal cycle of leydig cells in the Japanese Jungle Crow (Corvus macrorhynchos) (Asian Journal of Medical and Biological Research, 2015)
The investigation was conducted to elucidate seasonal histomorphological changes of Leydig cells in Japanese Jungle crows (Corvus macrorhynchos). All adult crows (n=12) were killed for H&E staining. Histologic data of Leydig cells regarding their locations in the interstitium, appearance and disappearance of lipoidal materials in their cytoplasm, precursor cells and fibroblasts are studied. In the nonbreeding season, in the interstitium, clusters of Leydig cells were found in abundant number. They looked foamy, white and easily visible. Their nuclei were found small and are located eccentrically. During recrudescence, the Leydig cell became less foamy and less white. In peak breeding season, the Leydig cells showed bigger in size and the nuclei became prominent. Cytoplasmic lipoidal material was lowest and cytoplasm was found dense pink. At the end of breeding period, heavy accumulation of lipid materials occurred in the Leydig cell. The clusters of Leydig cells were visible and looked white and foamy again. During this transition, disintegration of Leydig cells occurred after pycnotic nuclei of Leydig cells were found. During involution, new generation of fibroblast like cells appeared in the interstitium. Within the fibroblast like cells, some of them became lipoidal by accumulating lipid materials. Thus a new generation of Leydig cells appeared in the interstitium. These lipoidal cells are thought to be a new generation of Leydig cells for the next breeding season. This study suggests that in seasonally breeding birds, new generation of Leydig cell is derived from fibroblast like cells of the interstitium.Asian J. Med. Biol. Res. June 2015, 1(1): 65-73